Effect of solid-to-fluid conductivity ratio on mixed convection and entropy generation of a nanofluid in a lid-driven enclosure with a thick wavy wall. (December 2018) - Pal, S.K.; Bhattacharyya, S.; Pop, I.
Highlights: A numerical study on the conjugate mixed convection of Cu-water nanofluid has been considered. An enclosure with thick wavy bottom wall is considered. The computational domain has been transformed into an orthogonal co-ordinate system. The governing equations along with the boundary conditions are solved through a finite volume. Results showed that heat transfer rate increases remarkably by adding the nanoparticles. Abstract: A numerical study on the conjugate heat transfer by mixed convection of a Cu-water nanofluid and conduction in a solid region is conducted in an enclosure with a thick wavy heated wall. The upper lid of the enclosure is made to slide horizontally at a constant speed, along with that the condition of heated outer boundary of the thick bottom wall leads to a mixed convection within the enclosure. The impact of the wavy fluid-solid interface, solid-to-fluid thermal conductivity ratio and nanoparticle volume fraction on the heat transfer characteristics is analyzed for different choice of the Richardson number. The computational domain is transformed into an orthogonal co-ordinate system. The transformed governing equations along with the specified boundary conditions are solved through a finite volume method for a wide range of Richardson number, nanoparticle volume fraction, wave amplitude, wave number and wall-to-fluid conductivity ratio for different Reynolds number. Results show that the heat transfer rate increases substantially due to the inclusion of nanoparticles. Heat transfer rate varies due to the variation of the solid-to-fluid conductivity ratio, amplitude and wave number of the wavy wall. The impact of the wavy surface is stronger when the solid conductivity is in the order of the conductivity of the fluid. The Bejan number and the entropy generation are determined to analyze the thermodynamic optimization of the conjugate mixed convection.